Tax Policy Responses To Covid-19 Crisis - Eri Kusnanto; Muhammad Rizal; Andrew Subhana (Nusantara: Jurnal Pengabdian kepada Masyarakat, 2021)
The COVID-19 pandemic has brought unprecedented challenges to the global economy, including Indonesia. The closure of business premises, social restrictions, and decreased consumer purchasing power are some of the consequences that must be addressed. In response to this crisis, the Indonesian government has attempted to mitigate the negative impact by issuing various tax policies aimed at supporting the business sector and increasing consumer purchasing power. These policies include tax incentives, tax rate reductions, and relief for small and medium-sized enterprises (SMEs) struggling to survive during the crisis. This article discusses the tax policies issued by the government in response to the COVID-19 crisis and their implications for the Indonesian economy.